Media and Elusive Democracy in China - Zhao, Yuezhi (Javnost-The Public, 2001)
This paper delineates the multiple meanings of democracy and offers a social historical analysis on media and democratisation in China. Notwithstanding conventional perceptions about a disjuncture between economic liberalisation and political repression in China, the suppression of popular quests for political participation and the deprivation of media freedom for a majority of the Chinese population preceded waves of capitalistic developments in post-Mao China. The notion of democracy, meanwhile, has undergone significant transformations. Many activists in the late 1970s advocated popular and participatory democracy. By 1989, democracy had taken an elitist and liberal character among its advocates. Since the mid-1990s, Chinese discourses on democracy have assumed more complicated dimensions with accelerated capitalist developments, deepened social stratification, and the replacement of students and intellectuals by disenfranchised workers, peasants, and Falun Gong practitioners as the main forces of social contestation. Many regime protesters no longer appeal to the liberal democratic discourse. Some reformers, meanwhile, embrace liberal democracy as a means of popular containment. Today, China's state-controlled and commercialised media are deeply embedded in the established market authoritarian social order. While the Party makes every effort to prevent horizontal communication between disenfranchised groups and established intellectuals confine their debates to elite journals and cyberspaces, the role of Chinese workers and peasants and their voices remain a key problematic for media and democratisation in China.